TADRIS MAHARAH AL QIRAAH FI ASHR AL AULAMAH - Abdul Basith (Jurnal Alsinatuna, 2016)
This article discusses about the criteria of reading skill development in globalization era and its curriculum development. Reading skill development is very important because Arabic language teachers are supposed to adapt to technology in order to make their students ready in facing the globalization challenge. Hopefully, in its process, it will maximize the use of audio-visual media and programmed learning media, develop higher order thinking, consider individual needs, and update teaching technique continuously. Moreover, the curriculum development should be based on today’s reading curriculum, the development of science and current global issues, and the use of newest technology product. In addition, it also focuses on the development of all reading skill elements, learners’ consciousness of all education level, and continuous curriculum evaluation to make it along with the era development.